2018
DOI: 10.1177/1464419318770893
|View full text |Cite
|
Sign up to set email alerts
|

Calculating method of the fatigue life for the main supporting bearing of mixing drum in concrete mixing truck when considering drum’s vibration

Abstract: It has been observed that there are many studies focusing on the vibration properties of bearings caused by manufacturing errors, assembly related errors, out-of-balance rotor rotation, cage instability, etc. But there are fewer research studies on the effect of rotor’s vibration on double-row rolling element bearings’ mechanical properties. In this paper, a calculating method has been established for bearing’s roller load and fatigue life when considering rotor’s vibration. And this model is applied to study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…The results obtained were consistent with L-P model. Yang and An (2018) studied the fatigue life of spherical roller bearing of mixing truck considering drum’s vibration based on the Miner’s rule. Results showed that the fatigue life when considering mix drum’s vibration was shorter than that without considering vibration.…”
Section: Introductionmentioning
confidence: 99%
“…The results obtained were consistent with L-P model. Yang and An (2018) studied the fatigue life of spherical roller bearing of mixing truck considering drum’s vibration based on the Miner’s rule. Results showed that the fatigue life when considering mix drum’s vibration was shorter than that without considering vibration.…”
Section: Introductionmentioning
confidence: 99%